2010
DOI: 10.1093/eurjhf/hfq099
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin‐25 is a marker of the response rather than resistance to exogenous erythropoietin in chronic kidney disease/chronic heart failure patients†

Abstract: AimsErythropoietin (EPO) resistance, an important cause of anaemia in patients with heart and renal failure, is associated with increased mortality. The hypothesis of the present study was that exogenous EPO decreases hepcidin levels and that the decrease in hepcidin levels upon EPO treatment is related to the bone marrow response. Methods and resultsIn the EPOCARES trial, patients with renal failure (glomerular filtration rate 20-70 mL/min), heart failure, and anaemia were randomized to receive 50 IU/kg/week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 35 publications
(62 reference statements)
9
58
1
9
Order By: Relevance
“…In HD patients on ESA, hepcidin did not predict which patients increase their hemoblobin after iron loading (17 ). As mentioned earlier, several investigators have reported a decrease in hepcidin concentrations after EPO administration (31,50,169,170 ). These findings again suggest that the erythroid demand for iron might be a more powerful regulator of hepcidin expression than inflammatory-or iron-induced hepcidin formation.…”
Section: Disorders Associated With Hepcidin Excessmentioning
confidence: 75%
See 2 more Smart Citations
“…In HD patients on ESA, hepcidin did not predict which patients increase their hemoblobin after iron loading (17 ). As mentioned earlier, several investigators have reported a decrease in hepcidin concentrations after EPO administration (31,50,169,170 ). These findings again suggest that the erythroid demand for iron might be a more powerful regulator of hepcidin expression than inflammatory-or iron-induced hepcidin formation.…”
Section: Disorders Associated With Hepcidin Excessmentioning
confidence: 75%
“…Virtually all studies on hepcidin in CKD patients revealed a strong positive relationship between hepcidin and ferritin concentrations. Some of these studies also demonstrated correlations between hepcidin and iron or transferrin saturation (169,170 ). Hepcidin in CKD also has been associated with iron-restricted erythropoiesis, as reflected by the relation of hepcidin with lower hemoglobin and/or reticulocyte counts (31,169,171 ).…”
Section: Disorders Associated With Hepcidin Excessmentioning
confidence: 97%
See 1 more Smart Citation
“…5 In another study, 6 hepcidin levels at 3-5 months post transplant remained unchanged compared to (high) pre-transplant values. On the other hand, hepcidin response to erythropoietin therapy has been examined in healthy volunteers 10 or chronic kidney disease 10,11 in whom erythropoietin (EPO) elicited a rapid and persistent drop in serum hepcidin levels. Therefore, we decided to investigate the long-term kinetics of hepcidin after HCT in a group of patients participating in a clinical trial of post-transplant DA with and without intravenous iron therapy.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…[12] , also a study on patients with combined heart, renal failure and anemia, hepcidin levels was increased in comparison to healthy reference populations. [18], [19], [20] In this study hepcidin was negatively correlated to serum hemoglobin, serum iron and total iron binding capacity (P<0.01). (Table 3), figure (3 increased interleukin-6, high sensitive CRP may contribute to this condition.…”
Section: Resultsmentioning
confidence: 49%